2004
DOI: 10.1128/jcm.42.5.1933-1939.2004
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of a Binary Toxin (Actin-Specific ADP-Ribosyltransferase) from Clostridium difficile

Abstract: In addition to the two large clostridial cytotoxins (TcdA and TcdB), some strains of Clostridium difficile also produce an actin-specific ADP-ribosyltransferase, called binary toxin CDT. We used a PCR method and Southern blotting for the detection of genes encoding the enzymatic (CDTa) and binding (CDTb) components of the binary toxin in 369 strains isolated from patients with suspected C. difficile-associated diarrhea or colitis. Twenty-two strains (a prevalence of 6%) harbored both genes. When binary toxin p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
87
2
4

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(98 citation statements)
references
References 53 publications
5
87
2
4
Order By: Relevance
“…0 to 12 . 0 % (Goncalves et al, 2004;Stubbs et al, 2000). All our strains had both components of the binary toxin, which was not always the case in the reports of other authors (Perelle et al, 1997).…”
Section: Traditional Methods* Pcrmentioning
confidence: 50%
See 1 more Smart Citation
“…0 to 12 . 0 % (Goncalves et al, 2004;Stubbs et al, 2000). All our strains had both components of the binary toxin, which was not always the case in the reports of other authors (Perelle et al, 1997).…”
Section: Traditional Methods* Pcrmentioning
confidence: 50%
“…The genetic diversity of strains producing both LCTs varies in different series, depending on the sporadic or epidemic character of each one (Kato et al, 2001;Spigaglia et al, 2001). Several authors report a high homogeneity of variant strains (Alfa et al, 2000;Pituch et al, 2001) and one study reported that strains producing binary toxin are usually epidemiologically unrelated and not derived from a common ancestor (Goncalves et al, 2004), although in this report the isolates were obtained from 17 different institutions. LCTs and binary toxin prevalence in C. difficile…”
Section: Traditional Methods* Pcrmentioning
confidence: 63%
“…It has been recognized previously that the presence of functional binary toxin genes encoded by the 4.3 kb CDT locus correlates well with variant toxinotypes including A + B + , A 2 B + and A 2 B 2 strains (Stubbs et al, 2000;Rupnik et al, 2001Rupnik et al, , 2003aGeric et al, 2004;Spigaglia & Mastrantonio, 2002;Goncalves et al, 2004). This study presents an overview of all of the known variant toxinotypes and has confirmed that the full-length CDT locus is found in variant toxinotypes with significantly changed LCT toxin genes (shown in bold in Table 1), whereas the truncated version of the CDT locus is predominant in variant toxinotypes with minor changes in the LCT toxin genes (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, binary toxin-producing strains often seem to be associated with community-acquired C. difficile infections (Terhes et al, 2004;Barbut et al, 2005). The prevalence of binary toxin-producing strains has been estimated to be between 1.6 and 6 % (Stubbs et al, 2000;Rupnik et al, 2001Rupnik et al, , 2003bGeric et al, 2003;Goncalves et al, 2004;Terhes et al, 2004; Alonso et al, 2005) et al, 2006), regions with significant similarity to binary toxin have been found to be present, representing a truncated CDT locus (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Five A þ B þ isolates (8 . 6 %) harboured binary-toxin genes, a prevalence similar to that reported by Goncalves et al (2004). Binary-toxin-positive strains were isolated from adult patients hospitalized at different times (between 1999 and 2001) and in different units, and were considered epidemiologically unrelated.…”
Section: Resultsmentioning
confidence: 58%